Peripheral artery disease and exertional leg symptoms in diabetes patients in Ghana. Issue 1 (December 2016) - Yeboah, Kwame; Puplampu, Peter; Ainuson, Joana; Akpalu, Josephine; Gyan, Ben; Amoah, Albert
Abstract Background Peripheral arterial disease (PAD) is a major health problem in diabetes patients in high-income countries, but the PAD burden in sub-Saharan Africa is largely undetermined. We studied the prevalence of PAD and exertional leg symptoms in diabetes (DM) patients in a tertiary hospital in Ghana. Methods In a case control study design, 485 DM and 330 non-diabetes participants were recruited. PAD was diagnosed as Ankle Brachial Index (ABI) < 0.9. Edinburgh Claudication Questionnaire (ECQ) was used to assess exertional leg symptoms. Results The overall prevalence of classical intermittent claudication was 10.3 % and ABI-diagnosed PAD was 26.7 %, with 3.5 % of the participants having both classic intermittent claudication and ABI-diagnosed PAD. The prevalence of exertional leg symptoms were similar in diabetes patients with and without PAD. In non-diabetes participants, intermittent claudication and rest pain were higher in PAD patients than in non-PAD participants. In multivariable logistic regression, intermittent claudication [OR (95 % CI), 3.39 (1.14 – 8.1), p  < 0.05] and rest pain [4.3 (1.58 – 9.67), p  < 0.001] were independently associated with PAD in non-diabetes group, and rest pain [1.71 (1.13 – 2.17), p  < 0.05] was associated with PAD in all participants. Conclusions There is high burden of PAD and exertional leg pains in DM patients in Ghana. PAD is expressed as intermittent claudication and rest pain in non-diabetes individuals.